Answer:
The values for expression is h = - 2 and k = 5
Step-by-step explanation:
Given algebraic expression can be written as :
2 x³ - 10 x² + 11 x - 7 = ( x - 4 ) × ( 2 x² + h x + 3 ) + k
Now opening the bracket
Or, 2 x³ - 10 x² + 11 x - 7 = x × ( 2 x² + h x + 3 ) - 4 × ( 2 x² + h x + 3 ) + k
Or, 2 x³ - 10 x² + 11 x - 7 = 2 x³ + h x² + 3 x - 2 x² - 4 h x - 12 +k
Or , 2 x³ - 10 x² + 11 x - 7 = 2 x³ + ( h - 2 ) x² + ( 3 - 4 h ) x - 12 + k
Now, equating the equation both sides
I.e - 10 = ( h - 2 )
Or , h - 2 = - 10
I.e , h = - 10 + 2
∴ h = - 2
Again , 11 = ( 3 - 4 h )
or, 11 = 3 - 4 h
or, 11 - 3 = - 4 h
or, 8 = - 4 h
∴ h =
I.e h = - 2
Again
- 7 = - 12 + k
Or, k = - 7 + 12
∴ k = 5
Hence The values for expression is h = - 2 and k = 5 . Answer
Answer:
119
Step-by-step explanation:
Answer:
Pete: 39, Linda: 42
Step-by-step explanation:
Suppose Pete has x dollars. If he has 3 dollars less than Linda, then Linda has 3+x dollars. Together, they have 81 dollars:
x+3+x=81
2x+3=81
2x=78
x=39
Since Pete has x dollars, and x=39, he has $39.
Linda has 3+x, which is 39+3 = $42
<em>I hope this helps! :)</em>
Associative property Says that you can add or multiply regardless of how the numbers are group